Supermicrosurgical Experience pertaining to Replantation of Tamai Zone 1 Fingertip Amputations - Pamuk, Çağdaş (Handchirurgie · Mikrochirurgie · Plastische Chirurgie, 2022)
With the advent of supermicrosurgery, the replantation of very distal finger amputations has become possible. The choice between replantation or flap surgeries in the treatment of Tamai Zone I finger amputations continues to be a matter of debate. This study aims to evaluate replantation results in Tamai Zone 1 finger amputations. The demographic characteristics and clinical results of 39 patients undergoing replantation for a Tamai Zone 1 finger amputation between 2018 and 2021 were retrospectively analyzed. The Cold Intolerance Severity Score (CISS), two-point discrimination test (2-PD) and Quick Disabilities of the Arm, Shoulder and Hand (QuickDASH) were calculated and recorded after a minimum follow-up period of 6 months. The great majority of patients were males (92.3%, n=36) who had suffered the injuries during work accidents (89.7%, n=35). The socioeconomic status of the patients showed a homogeneous distribution. Replant survival was achieved in 69.2% (n=27) of all fingers. The duration of the surgical procedure in patients who underwent vein repair was significantly longer (p<0.001). However, there was no significant relationship between vein repair and survival rate (p=0.348). This study shows that replantation is a surgical intervention that should be given priority in patients with Tamai Zone 1 amputations. In most cases of unsuccessful replantation, secondary recovery results are also acceptable. Future studies with larger case series are needed.Die Fortschritte in der Supermikrochirurgie machen Replantationen extrem peripherer Fingeramputationen möglich. Ob bei einer Fingerendgliedamputation in Zone Tamai I eine Replantation oder eine lappenplastische Defektdeckung erfolgen sollte, ist jedoch weiterhin Gegenstand von Diskussionen. Diese Studie untersucht deshalb die Ergebnisse nach Replantation von Fingerendgliedamputation in Zone Tamai I. Die demographischen Daten und klinischen Ergebnisse von 39 Patienten, bei denen im Zeitraum von 2018 bis 2021 eine Replantation bei einer Fingerendgliedamputation in Zone Tamai I erfolgte, wurden retrospektiv analysiert. Dabei wurde die Kälteempfindlichkeit mittels des Cold Intolerance Severity Scores (CISS), die Zwei-Punkt-Diskrimination und der Quick-DASH erfasst, wobei die Nachuntersuchungszeit minimal 6 Monate betrug. Die Mehrheit der Patienten war männlich (92,3%, n=36) und hatte sich die Verletzung bei einem Arbeitsunfall zugezogen (89,7%, n=35). In 27 Fällen (69,2%) überlebte das Replantat. Erfolgte eine Venenanastomose, dauerte die Operation signifikant länger (p<0,001). Allerdings hatte die Durchführung einer Venenanastomose keinen signifikanten Einfluss auf die Überlebensrate des Replantates (p=0,348). Aufgrund der Ergebnisse geben wir der Replantation bei Fingerendgliedamputationen in Zone Tamai I den Vorzug gegenüber sonstigen Maßnahmen. Ist diese nicht erfolgreich, lässt sich trotzdem meist durch eine sekundäre Wundheilung ein akzeptables Resultat erzielen. Weitere Studien mit dem Ziel der Entwicklung eines Therapiealgorithmus sind sinnvoll.
Keywords: Tamai Zone 1; supermicrosurgery; vein repair; artery repair